The power of lived experience in optimizing US policymakers’ engagement with substance use research: A series of rapid-cycle randomized controlled trials - Elizabeth C. Long; Riley Loria; Jessica Pugel; Patrick O’Neill; Camille C. Cioffi; Charleen Hsuan; Glenn Sterner; D. Max Crowley; J. Taylor Scott (Drug and Alcohol Dependence Reports)
Background: Research can inform policies on substance use/substance use disorders (SU/SUDs), yet there is limited experimental investigation into strategies for optimizing policymakers’ engagement with SU/SUD research. This study tested the use of narratives to boost policymakers’ research engagement. Methods: In five rapid-cycle randomized controlled trials, SU/SUD research fact sheets were emailed to US legislative policymakers. We tested the use of narratives on the number of email opens, fact sheet clicks, and replies, relative to control emails without narratives. Narratives described lived experience with SU/SUD or motivations to study SU/SUD. The sender was a person with lived experience who authored the narrative or an author of the fact sheet. Results: When the narrative was about the sender’s own lived experience (Trial 1), or when the narrative was about the sender's motivations to study SU/SUDs (Trial 2), the fact sheet was clicked more than the control (p=.049; p=.012; respectively). When the narrative was about someone else’s experience (Trials 3 and 4), the email was opened (p’s<.001) and replied to (p’s<.001) less, and the fact sheet was clicked (p’s<.001) less. Lastly, emails with lived experience narratives were replied to more than the control, regardless of sender (fact sheet author: p=.028; narrative author: p=.002; Trial 5), but were opened more if the sender authored the narrative (p<.001). Conclusions: Policymakers’ engagement with SU/SUD research generally increased when the sender was telling their own story. This work highlights the power of people with lived experience and informs strategies for optimizing policymakers’ engagement with SU/SUD research.